Pengaruh Burn Out Dan Fasilitas Kerja terhadap Efektivitas Kerja Pada PT Bina Artha Semesta Kota Depok - Mohamad Saefoedin; Eko Sudarso (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This research aims to determine the influence of Burn Out and Work Facilities on Work Effectiveness at PT Bina Artha Semesta Depok City, both partially and simultaneously. This research method uses quantitative methods with a sample size of 99 respondents. The data collection technique is by means of a questionnaire, and the data analysis techniques are validity test, reliability test, simple linear analysis, multiple linear analysis, correlation coefficient, coefficient of determination, and hypothesis testing. The results of this research show that there is a significant influence between Burn Out and Work Facilities on Work Effectiveness simultaneously. This can be seen from the value of the multiple linear regression equation, namely Y = 15.066 + 0.485+ 0,159 X2 The constant shows 15.066, meaning that if there is a change in the constant of the independent variable (X1 and X2 values = 0) then the value of the dependent variable Work Effectiveness (Y) is 15.066. The multiple correlation coefficient value shows that the variables Burn Out (X1) and Work Facilities (X2) have a significant influence on Work Effectiveness (Y), with a significant change value F of 0.000 or less than 0.05. The correlation value obtained is 0.612, which is between 0.600 - 0.799 with a strong relationship level. The coefficient of determination value is 0.719, so it can be concluded that the Burn Out (X1) and Work Facilities (X2) variables influence the Work Effectiveness variable (Y) by 71.9% while the remaining 28.1% is influenced by other factors. Simultaneously testing the hypothesis obtained a calculated F value > F table or (11.789 > 3.09), this was also strengthened by a ρ value < Sig.0.05 or (0.000 < 0.05). This shows that there is a significant simultaneous influence between Burn Out and work facilities on Work Effectiveness at PT Bina Artha Semesta.